PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI ARITMATIKA SOSIAL MENGGUNAKAN APLIKASI GOOGLE CLASSROOM PADA SISWA SMP NEGERI 1 SIBORONGBORONG - ATINURIDA MANURUNG (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
This classroom action research aims to describe the improvement of the process and learning outcomes of social arithmetic material for mathematics students in grades 7-2 of SMP Negeri 1 Siborongborong through the use of the Google Classroom application. This research was conducted through two cycles. The type of research carried out is Classroom Action Research (CAR) with data collection techniques through learning outcomes test sheets. The data analysis technique used descriptive technique. The subjects in this study were grade 7B students of SMP Negeri 1 Siborongborong. The results of this study indicate that the use of the Google Classroom application can improve student learning processes and outcomes. The average increase in student learning outcomes has increased from 55.00 in the initial conditions, to 66.88 in the first cycle, and at the end of the second cycle to 78.44 with the level of mastery learning which also increases in each cycle, namely 10 students ( 31.25%) in the initial condition, to 53.46% or 17 students, and in the last cycle to 87.50% or 28 students. From the explanation above, it can be concluded that the use of the Google Classroom application is proven to be able to improve the process and learning outcomes of social arithmetic material for 7B grade students of SMP Negeri 1 Siborongborong. From the explanation above, the indicators of learning success have been achieved in the second cycle, so that the implementation of learning improvements is declared complete and complete in the second cycle. ABSTRAKPenelitian tindakan kelas ini bertujuan untuk mendeskripsikan peningkatan proses dan hasil belajar matematika materi aritmatika sosial siswa kelas 7-2 SMP Negeri 1 Siborongborong melalui penggunaan aplikasi Google Classroom. Penelitian ini dilaksanakan melalui dua siklus. Jenis penelitian yang dilaksanakan adalah Penelitian Tindakan Kelas (PTK) dengan teknik pengumpulan data melalui lembar tes hasil belajar. Teknik analisa data menggunakan teknik desktiptif. Subjek dalam penelitian ini adalah siswa kelas 7B SMP Negeri 1 Siborongborong. Hasil penelitian ini menunjukkan melalui penggunaan aplikasi Google Classroom dapat meningkatkan proses dan hasil belajar siswa. Peningkatan rata-rata hasil belajar siswa mengalami peningkatan dari 55,00 pada kondisi awal, menjadi 66,88 pada siklus pertama, dan pada akhir siklus kedua menjadi 78,44 dengan tingkat ketuntasan belajar yang juga meningkat pada setiap siklusnya, yaitu 10 orang siswa (31,25%) pada kondisi awal, menjadi 53,46% atau 17 siswa, dan pada siklus terakhir menjadi 87,50% atau 28 siswa. Dari penjelasan di atas dapat disimpulkan bahwa penggunaan aplikasi Google Classroom terbukti dapat meningkatkan proses dan hasil belajar matematika materi aritmatika sosial siswa kelas 7B SMP Negeri 1 Siborongborong. Dari penjelasan di atas indikator keberhasilan pembelajaran telah tercapai pada siklus kedua, sehingga pelaksanaan perbaikan pembelajaran dinyatakan selesai dan tuntas pada siklus kedua.